Media Komunikasi Pemasaran Dalam Usaha Rest Area Di Jonggol Jawa Barat - Akim, Mulya; Sukarelawati, Sukarelawati; Kusumadinata, Ali Alamsyah (CommLine, 2023)
The object in this study is the Rest Area located in Jonggol, West Java. The purpose of the study aims to explain the function of social media, especially Whatsapp as a marketing communication medium by business managers in the rest area. Marketing communication is carried out to increase sales of each business actor, in the process of increasing sales, each business actor carries out different ways of promotion. The decrease in income was due to the implementation of PPKM which reduced the number of visits and visits to tourist sites. Research climbing using qualitative with descriptive methods. Data collection was carried out by observation and interview techniques. The data analysis technique used uses data presentation and is developed into a descriptive narrative with a theoretical approach that is in accordance with marketing communication. The results of this study show that consumers' purchasing decisions in Jonggol Rest Area using Whatsapp communication media as a promotion have a good relationship between managers, stall tenants, and consumers.